The gut microbiome in solid organ transplantation. (30th September 2020) - Baghai Arassi, Maral; Zeller, Georg; Karcher, Nicolai; Zimmermann, Michael; Toenshoff, Burkhard
Abstract: Despite ground‐breaking advances in allogeneic transplantation, allograft rejection and immunosuppressant‐specific complications remain a major challenge in transplant medicine. Growing evidence suggests the human gut microbiome as a potential contributor to transplant outcome and patient health. After breakthrough findings in haematopoietic stem cell transplantation (HSCT), the relevance of the microbiome in solid organ transplantation (SOT) is becoming increasingly clear. Here, we review the role of the microbiome in SOT focusing on its significance for transplant‐associated complications such as allograft rejection and infections, and highlight its potential impact on immunosuppressive treatment. Moreover, we shed light on the emerging role of the microbiome as a diagnostic biomarker and therapeutic target and discuss current microbial intervention strategies. In addition, this review includes some practical considerations in designing clinical microbiome trials and offers some advice for the interpretation of the resulting data. Further investigation of the gut microbiome harbours countless clinical application possibilities and holds great promise of having a lasting impact on transplant medicine.